Early age-related maculopathy in the cardiovascular health study. - Klein, Ronald; Klein, Barbara E K; Marino, Emily K; Kuller, Lewis H; Furberg, Curt; Burke, Gregory L; Hubbard, Larry D (Ophthalmology, 2003)
OBJECTIVE: To describe the prevalence of early age-related maculopathy (ARM) and its relation to atherosclerosis, lipids, hypertension, and inflammatory factors in a population studied for cardiovascular disease risk factors and outcomes. DESIGN: Population-based cohort study. PARTICIPANTS: A biracial population of 2361 adults (ranging from 69-97 years of age; 1998 whites and 363 blacks) living in four US counties (Allegheny County, Pennsylvania; Forsyth County, North Carolina; Sacramento County, California; and Washington County, Maryland) were examined during the interval from 1997 to 1998. METHODS: Drusen and other lesions typical of ARM were identified by examining a 45 degrees color fundus photograph of one eye of each participant and classified by means of a modification of the Wisconsin Age-Related Maculopathy Grading System. MAIN OUTCOME MEASURES: Early ARM. RESULTS: Early ARM was present in 15.5% and late ARM in 1.3% of the cohort. The overall prevalence of any ARM was lower in blacks (9.1%) compared with whites (18.2%). While controlling for age, race, gender, and total calories consumed in the diet, factors associated with ARM were cerebral white matter disease as detected by magnetic resonance imaging (odds ratio [OR], 1.50; 95% confidence interval [CI], 1.05, 2.16, P = 0.027), and lower serum total cholesterol (OR, per 10 mg/dl increase 0.95; 95% CI, 0.91, 0.98, P = 0.02). There were no associations between hypertension, blood pressure, common carotid artery plaque, or any systemic inflammatory factors studied and early ARM. CONCLUSIONS: This population-based study documents the higher prevalence of ARM in whites compared with blacks. Although an association was found between signs of white matter disease and early ARM, there was no evidence of an association of ARM with either hypertension or inflammatory factors.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Arteriosclerosis; Blood Pressure; C-Reactive Protein; California; Cohort Studies; Diet; European Continental Ancestry Group; Female; Humans; Hypertension; Leukocyte Count; Longitudinal Studies; Macular Degeneration; Male; Mid-Atlantic Region; North Carolina; Prevalence; Prospective Studies; Risk Factors; Serum Albumin